Balance impairment in pediatric charcot–marie–tooth disease. Issue 3 (15th May 2019) - Estilow, Timothy; Glanzman, Allan M.; Burns, Joshua; Harrington, Ann; Cornett, Kayla; Menezes, Manoj P.; Shy, Rosemary; Moroni, Isabella; Pagliano, Emanuela; Pareyson, Davide; Bhandari, Trupti; Muntoni, Francesco; et al.
ABSTRACT: Introduction : Balance impairment contributes to gait dysfunction, falls, and reduced quality of life in adults with Charcot–Marie–Tooth disease (CMT) but has been minimally examined in pediatric CMT. Methods : The CMT Pediatric Scale (CMTPedS) was administered to 520 children with CMT. Associations between balance function (Bruininks–Oseretsky Test of Motor Proficiency [BOT‐2]) and sensorimotor and gait impairments were investigated. Results : Daily trips/falls were reported by 42.3% of participants. Balance (BOT‐2) varied by CMT subtype, was impaired in 42% of 4‐year‐olds, and declined with age ( P < 0.001). Vibration ( P < 0.001), pinprick ( P < 0.004), ankle dorsiflexion strength ( P < 0.001), and foot alignment ( P < 0.004) were associated with BOT‐2 balance (adjusted R 2 = 0.28). The visual dependence of balance increased with age. Discussion : Balance impairment occurs from a young age in children with CMT. Balance intervention studies are required in pediatric CMT and should consider the degree of sensorimotor impairment, foot malalignment, and visual dependence. Muscle Nerve, 2019